1
$\begingroup$

The sequence $\{a_0,a_1,...a_x\}$ has closed form $a_n=\sum_{i=0}^{\infty} \Delta^i(0) {n \choose i}$ where $\Delta a_n$ denotes the operation mapping $a_n$ to $a_{n+1}-a_n$ and $\Delta^i(0)$ is shorthand for this operation iterated $i$ times on $a_n$ and then evaluated at $n=0$. Furthermore $\sum_{n=0}^{x} {n \choose k}={x+1 \choose k+1}$ and a polynomial of degree $n$ can be determined uniquely from $n+1$ points. Combining these results we may get:

$$\sum_{k=1}^{x} k^1=1{x+1 \choose 2}$$

$$f(1)=1$$

$$\sum_{k=1}^{x} k^2=1{x+1 \choose 2}+2{x+1 \choose 3}$$

$$f(2)=(1,2)$$

$$\sum_{k=1}^{x} k^3=1{x+1 \choose 2}+6{x+1 \choose 3}+6{x+1 \choose 4}$$

$$f(3)=(1,6,6)$$

Question

Is there expression for $f$ without the use of $\Delta^i(0)$?

$\endgroup$
1
$\begingroup$

See https://en.wikipedia.org/wiki/Stirling_numbers_of_the_second_kind .

$\Delta^i x^n=\sum\limits_{j=0}^i (-1)^{i-j}\binom{i}{j}(x+j)^n$

Set $x:=0$.

E.g.: $f(3)=(\sum\limits_{j=0}^1 (-1)^{1-j}\binom{1}{j}j^3,\sum\limits_{j=0}^2 (-1)^{2-j}\binom{2}{j}j^3,\sum\limits_{j=0}^3 (-1)^{3-j}\binom{3}{j}j^3)$


It’s a method of the “Discrete Mathematics”. Be $f(x)$ a function without poles.

Identity operator $I$: $If(x):=f(x)$

Shift operator $E$: $Ef(x):=f(x+1)$

Important: $I$ and $E$ are linear operators.

Difference Operator $\Delta$: $\Delta:=E-I$

=> $\Delta f(x)=(E-I)f(x)=Ef(x)-If(x)=f(x+1)-f(x)$

Therefore $\Delta^i f(x)=(E-I)^i f(x)=\sum\limits_{k=0}^i (-1)^{i-k}\binom{i}{k}E^k f(x)=\sum\limits_{k=0}^i (-1)^{i-k}\binom{i}{k}f(x+k)$.

Set $f(x):=x^n$ (here: $x\in\mathbb{R}_0^+$), then you get the formula for $\Delta^i x^n$.

$\endgroup$
  • $\begingroup$ Can you show how you derived $\Delta^i x^n$ please. $\endgroup$ – Ahmed S. Attaalla Jul 4 '16 at 12:59
  • $\begingroup$ Also so $f(n)=(1!s(n,1),2!s(n,2),3!s(x,3),...,n!s(n,n))$ correct? $\endgroup$ – Ahmed S. Attaalla Jul 4 '16 at 13:08
  • 1
    $\begingroup$ That's right. And I have added the explanation above. $\endgroup$ – user90369 Jul 4 '16 at 13:35
  • $\begingroup$ Made a typo $f(n)=(1!s(n,1),2!s(n,2),3!s(n,3),...,n!s(n,n))$ $\endgroup$ – Ahmed S. Attaalla Jul 4 '16 at 13:46
  • 1
    $\begingroup$ @Ahmed S. Attaalla : I hope that you mean with $s(n,k)$ the stirling numbers of the second kind - but they are written e.g. $S(n,k)$. Please don't mix it up with the stirling numbers of the first kind. $\endgroup$ – user90369 Jul 5 '16 at 10:30

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.